Hydrocele of the Canal of Nuck Presenting as Inguinal Swelling in an Adult Female: A Case Report. - Pathak, Surendra; Kumar, Yogesh; Verma, Vishal; Yadav, Sahil; Pandey, Vaibhav Mani (Journal of Neonatal Surgery, 2025)
INTRODUCTION: Foreign body aspiration is a significant cause of morbidity and mortality in children and presents distinct Hydrocele of the canal of Nuck is a rare condition in adult females and is often misdiagnosed as an inguinal hernia or other groin pathology (1,2). We report the case of a 31-year-old female who presented with a six-month history of right-sided inguinal swelling. Ultrasonography revealed a lobulated tubular cystic lesion extending from the intrapelvic region into the right inguinal canal and labia majora without evidence of bowel or omental herniation, suggestive of an encysted hydrocele of the canal of Nuck (3,6). The patient underwent surgical excision of the cystic sac with ligation of the proximal patent processus vaginalis under spinal anesthesia. The postoperative course was uneventful. This case highlights the need to consider canal of Nuck hydrocele as a differential diagnosis in females presenting with inguinal swelling and emphasizes the role of ultrasonography as a reliable first-line diagnostic modality (5,8).